Perancangan Sistem Informasi Customer Relationship Management (CRM) untuk Meningkatkan Loyalitas dan Pelayanan Customers Berbasis Web dengan Model Waterfall - Hadi Zakaria; Aida Eka Marlia (Program Studi Teknik Informatika Universitas Pamulang, 2019)
Customer Relationship Management (CRM) is defined as a single unit of sales, marketing and service strategies that prevent uncoordinated work activities between parts well and that depends on coordinated company actions. In this study, the system development model used using the waterfall model is a classic model that is systematic, sequential in building software (Mira, 2013). The advantage of this model is that the development process is very structured and systematic, through the definition of needs, so that gaps or gaps that occur between the needs and the system produced can be reduced and produce clear development direction for management. Until now, data services are still not integrated, resulting in unsatisfactory service to consumers, the absence of a customer complaint system so that companies can find out complaints in the form of criticism and suggestions to improve service to customers. In this study will build CRM on PT. Srikandi Diamond Motor by using the Waterfall model so that the system is integrated and can improve service to customers and make customer complaints so that companies can find out complaints in the form of criticism and suggestions to improve service to customers. Based on the results of the implementation and testing of this system it can be concluded that the application of data processing systems has been integrated with each other so that it can improve the quality of service to customers, in the implementation of the customer complaint system has been very helpful for companies in knowing complaints in the form of criticism and suggestions to improve service to customers.